Comparative ontogeny of the feeding apparatus of sympatric drums (Perciformes: Sciaenidae) in the Chesapeake Bay. (12th November 2015) - Deary, Alison L.; Hilton, Eric J.
ABSTRACT: The anatomy of the feeding apparatus in fishes, including both oral and pharyngeal jaw elements, is closely related to the ecology of a species. During ontogeny, the oral and pharyngeal jaws undergo dramatic changes. To better understand how such ontogenetic changes occur and relate to the feeding ecology of a species, ontogenetic series of four closely related members of the family Sciaenidae ( Cynoscion nebulosus, Cynoscion regalis, Micropogonias undulatus, and Leiostomus xanthurus ) were examined. Sciaenids were selected because as adults they exhibit considerable specialization of the feeding apparatus correlated with differences in foraging habitats. However, it is not clear when during ontogeny the structural specializations of the feeding apparatus develop, and thereby enable early life history stage (ELHS) sciaenids to partition their foraging habitats. A regression tree was recovered from the analysis and three divergences were identified during ontogeny. There are no measurable differences in elements of the feeding apparatus until the first divergence at 8.4 mm head length (HL), which was attributed to differences in average gill filament length on the second ceratobranchial. The second divergence occurred at 14.1 mm HL and was associated with premaxilla length. The final divergence occurred at 19.8 mm HL and was associated with differences in the toothed area of the fifth certatobranchial. These morphological divergences suggest that ELHS sciaenids may be structurally able to partition their foraging habitats as early as 8.4 mm HL. J. Morphol. 277:183–195, 2016. © 2015 Wiley Periodicals, Inc.